Large-scale agricultural investments and local food security – Evidence from a mixed-method case study in Benin - Anika Muder; Jonas Luckmann; Julia C. Schmid (Food Security, 2024)
Abstract Large-scale agricultural investments (LSAIs) and their impacts on local communities in host countries have been controversially discussed in recent years. As scholars increasingly call for more structured and comprehensive analyses, we develop a mixed-method approach using an expanded version of the “Right to Food” (RtF) framework to systematically investigate the local food security impacts of a recently established tomato-producing LSAI in Central Benin, West Africa. We find that the LSAI keeps natural resources as accessible as possible for the local community and provides employment opportunities, leading to higher dietary diversity of employees and multiplier effects in the local economy. At the same time, we find inequalities regarding the compensation of former land users as well as high job insecurity for temporary laborers who face high transportation costs to reach the LSAI. We argue that fair and inclusive compensation, improved access to markets and machinery, access to natural resources for often overlooked groups (pastoralists, hunters, fishermen) and social infrastructure are crucial factors in promoting positive outcomes of LSAIs on communities and that strong local institutions play a key role for achieving this. We conclude that the specific characteristics of our case (relatively small size, labor-intensive crop, focus on regional markets) provide favorable conditions for positive impacts on local food security. We encourage further, structured mixed-method studies, ideally including longitudinal and comparative research designs, to investigate the multidimensional effects related to the establishment of LSAIs. The extended RtF framework can thereby serve as a structural lens to systematically analyze the findings.
Additional information: Q12;Q15;I39
Keywords: 330; Foreign direct investment; Land acquisition; Land deal; Land grabbing; Land transfer; Livelihood